"Gold" Pressed Essential Oil: An Essay on the Volatile Fragment from Citrus Juice Industry By-Products Chemistry and Bioactivity. (4th October 2017) - Kapsaski-Kanelli, V. N.; Evergetis, E.; Michaelakis, A.; Papachristos, D. P.; Myrtsi, E. D.; Koulocheri, S. D.; Haroutounian, S. A.
Abstract : Present essay explores the potentials of Citrus juice industry's by-products as alternative bioactive natural products resources. Four crude Cold Pressed Essential Oils (CPEOs), derived from orange, lemon, grapefruit, and mandarin, were studied. All CPEOs were subjected to water distillation, in order to obtain the volatile fragment, which was further fractionated with respect to distillation period in two parts, concluding to eight samples. These samples along with the four original CPEOs were assessed in relation to their phytochemical content and their repellent and larvicidal properties against Asian Tiger Mosquito. The volatiles recovery rates ranged from 74% to 88% of the CPEO. Limonene presented a significant increase in all samples ranging from 8% to 52% of the respective CPEO's content and peaked in mandarin's 2nd volatile fragment which comprised 97% of the essential oil. The refinement process presented clear impacts on both bioassays: a significant increase in larvicidal potency was observed, annotated best by the improvement by 1100% and 1300% of the grapefruit volatile fractions; repellence testing provided only one significant result, the decrease of landings by 50% as a response to mandarin's second volatile fraction. The applied methodology thus may be considered for the improvement of Citrus juice industry's by-products chemistry and bioactivity.